2011
DOI: 10.1097/brs.0b013e318a511b0e
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of BMP4, IL6, Leptin, MMP3, and MTNR1B Gene Promoter Polymorphisms and Adolescent Idiopathic Scoliosis

Abstract: the genetic effect of promoter polymorphisms of BMP4, IL6, leptin, MMP3, and MTNR1B can be synergistic for susceptibility to AIS. The combinatorial effect can modulate the final biological impact of many susceptibility polymorphisms; therefore, this should be considered at the comparison of results from case-control studies of different populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 37 publications
4
55
0
12
Order By: Relevance
“…[16][17][18] Several genetic studies failed to identify mutations in the genes responsible for the production of melatonin. [19][20][21][22][23][24] There is only one study suggesting that the MTNR1B gene responsible for a melatonin receptor is a predisposing factor for the development of AIS. 25 Recent studies focus on the role of Gi proteins on the cellular membrane, which are in contact with the melatonin receptors and play an important role in the phosphorylation of other cell proteins, such as protein kinase A and C. The role of Gi proteins seems to be crucial, leading to a transmembrane dysfunction, which in turn affects the transfer of the melatonin hormonal message inside the cell by altering c-AMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Several genetic studies failed to identify mutations in the genes responsible for the production of melatonin. [19][20][21][22][23][24] There is only one study suggesting that the MTNR1B gene responsible for a melatonin receptor is a predisposing factor for the development of AIS. 25 Recent studies focus on the role of Gi proteins on the cellular membrane, which are in contact with the melatonin receptors and play an important role in the phosphorylation of other cell proteins, such as protein kinase A and C. The role of Gi proteins seems to be crucial, leading to a transmembrane dysfunction, which in turn affects the transfer of the melatonin hormonal message inside the cell by altering c-AMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…The MMP3 À1171 5A allele enhanced in vivo gene expression by two-to fourfold than that of MMP3 À1171 6A allele. 6 A case-control study conducted by Aulisa et al 5 in 2007 was the first one which investigated the role of the IL-6 and MMP3 functional polymorphisms in the pathogenesis of AIS and concluded that the MMP3 (À1171 5A/6A) and IL-6 (À174G/C) promoter polymorphisms constitute important factors for the genetic predisposition to scoliosis. No significant differences in the frequencies of the BMP4, Leptin, IL-6, MMP3, and MTNR1B polymorphisms were reported throughout the cases and controls in a Hungarian population sample.…”
mentioning
confidence: 98%
“…The transfection of IL-6 À174C alleles into HeLa cells in vitro has resulted in a decrease in IL-6 production compared to that of IL-6 À174G. 6 Matrix metalloproteinases (MMPs) constitute the largest family of enzymes responsible for degrading various extracellular matrix components. An adenine insertion/deletion polymorphism (5A/6A) at position À1171 of the promoter region of MMP3 influences transcription factor binding and promoter activity.…”
mentioning
confidence: 99%
See 2 more Smart Citations